2015
DOI: 10.1007/s00231-015-1551-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of thermal contact conductance for nominally flat metallic contact

Abstract: Joint thermal contact conductance h r Radiation heat transfer coefficient ΔT Temperature drop across the interface H Vickers hardness k Effective thermal conductivity, k = 2k 1 k 2 / (k 1 + k 2 ) m Effective arithmetic average slope, m = m 2 1 + m 2 2 P Normalized pressure, P = P H P Applied pressure Q Heat flow rate R qEffective root mean square roughness,U Q 1 , U Q 2 Uncertainties in the estimation of heat fluxes, Q 1 and Q 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Due to the temperature of the contact surfaces between the copper bonds and the blade being less than 427 • C, the thermal radiation resistance can be neglected (Bahrami et al, 2004a). The thermal contact resistance model can be seen to in other works (Zheng et al, 2014;Shi et al, 2018;Tariq et al, 2016;Yovanovich et al, 2006;Grujicic et al, 2005;Bahrami et al, 2004b) and our previous research (Dai et al, 2020b).…”
Section: Model Equations and Boundary Conditionsmentioning
confidence: 65%
See 1 more Smart Citation
“…Due to the temperature of the contact surfaces between the copper bonds and the blade being less than 427 • C, the thermal radiation resistance can be neglected (Bahrami et al, 2004a). The thermal contact resistance model can be seen to in other works (Zheng et al, 2014;Shi et al, 2018;Tariq et al, 2016;Yovanovich et al, 2006;Grujicic et al, 2005;Bahrami et al, 2004b) and our previous research (Dai et al, 2020b).…”
Section: Model Equations and Boundary Conditionsmentioning
confidence: 65%
“…The temperature variation in and fluctuation of the molten pool can reflect the transient accumulation of heat, which affects the cooling rate and the quality of the surfacing zone (Näsström et al, 2019;Wahab et al, 1998). Based on the calculation results of the single and double ARM-repair height models, the double ARM-repair height is set as the z axis coordinate of the weld seam cross section.…”
Section: Comparison Of Temperature Distribution Of Weld Seammentioning
confidence: 99%
“…Their findings revealed that rough surfaces exhibit higher TCR under the same conditions [20]. The changes in the hardness as well as the thermal conductivity of the contacting body affect the TCC, for example see [21][22][23]. Their research results indicated that the material with lower yield strength or hardness value and high thermal conductivity shows better improvement in TCC.…”
Section: --------------mentioning
confidence: 99%
“…For the purpose of quantifying the thermal contact resistance values of various cases and evaluating the effect of physical parameter, many experimental apparatuses have been utilized for the measurements as shown in Fig. 3 [1][2][3][4][5][6]. Fig.…”
Section: Experimental Apparatusesmentioning
confidence: 99%